Cadium accumulation and elimination in the tissues of Oreochromis sp - Thang, Nguyen Quoc; Tan, Le Van; Kim Phuong, Nguyen Thi (Vietnam Journal of Chemistry, 2017)
The accumulation and elimination of Cd on Oreochromis sp. tissues were studied in exposure phase and recovery phase. In the exposure phase, the mean rate of Cd accumulation in the Oreochromis sp. tissues was in the order liver >> gill >> muscle. Cd accumulation in these tissues increased with increases in Cd concentrations in the water or as time proceeded. In the recovery phase, the order elimination in the tissues was also gill > muscle > liver. Short-term depuration (10 days), quick decrease of Cd in gill and muscle of Oreochromis sp. were observed. Keywords. Cadmium, accumulation, depuration, Oreochromis sp